VD_FINDINFO ML / 2010 / 167 vom 4. März 2010 - VD Tribunal cantonal (2010)
MAINLEVÉE DÉFINITIVE, DÉCISION DE COTISATIONS, COTISATION AVS/AI/APG | 97 al. 1 LAVS, 80 LP, 52 LPGA, 54 al. 1 LPGA, 34a RAVS